A case report of focal dermal hypoplasia-Goltz syndrome - Sheela Bharani; Sejal Thakkar (Wolters Kluwer Medknow Publications, 2013)
Goltz syndrome is a rare multisystem disorder with cutaneous, ocular, dental and skeletal abnormalities. Other mesoectodermal abnormalities are also present. Its hallmark is thinning of the dermis resulting subcutaneous fat herniation. The present case is a 5 year old girl having linear skin atrophy with fat herniation, skeletal abnormalities in the form of polysyndactyly, facial asymmetry, squint with coloboma iris, deformed pinna, abnormal dentition, umbilical hernia along with osteopathia striata of long bones which is consistent with Goltz syndrome. We are presenting this case due to its rarity.